(untitled) (World Economics and Finance Bulletin, 2023)
This article discusses the causes and effects of national, international, and global migration at the macro, micro, and meso levels within political analysis. It looks deeply into the theoretical aspects of urbanization and demographics, giving the latest statistics for migration. Lastly, the article examines measures implemented by Uzbekistan’s government to regulate migration and presents the country’s key concepts for controlling migration in its 2030 development strategy.